RETRACTED: vB-ApyS-JF1, the First Trueperella pyogenes Phage, Shows Potential as an Alternative Treatment Strategy for Trueperella pyogenes Infections - Ji, Yalu; Song, Liran; Zhou, Zuoyong; Liu, Xiao; Li, Fengyang; Guo, Zhimin; Guan, Yuan; Yang, Li; Feng, Xin; Sun, Changjiang; Lei, Liancheng; Han, Wenyu; et al. (Frontiers in Microbiology, 2021)
Trueperella pyogenes (T. pyogenes) is an important opportunistic animal pathogen that causes huge economic losses to the animal husbandry industry. The emergence of bacterial resistance and the unsatisfactory effect of the vaccine have prompted investigators to explore alternative strategies for controlling T. pyogenes infection. Due to the ability of phages to kill multidrug-resistant bacteria, the use of phage therapy to combat multidrug-resistant bacterial infections has attracted attention. In this study, a T. pyogenes phage, vB-ApyS-JF1 (JF1), was isolated from sewage samples, and its whole genome and biological characteristics were elucidated. Moreover, the protective effect of phage JF1 on a mouse bacteremic model caused by T. pyogenes was studied. JF1 harbors a double-stranded DNA genome with a length of 90,130 bp (30.57% G + C). The genome of JF1 lacked bacterial virulence-, antibiotic resistance- and lysogenesis-related genes. Moreover, the genome sequence of JF1 exhibited low coverage (< 6%) with all published phages in the NCBI database, and a phylogenetic analysis of the terminase large subunits and capsid indicated that JF1 was evolutionary distinct from known phages. In addition, JF1 was stable over a wide range of pH values (3 to 11) and temperatures (4 to 50°C) and exhibited strong lytic activity against T. pyogenes in vitro. In murine experiments, a single intraperitoneal administration of JF1 30 min post-inoculation provided 100% protection for mice against T. pyogenes infection. Compared to the PBS treatment group, JF1 significantly (P < 0.01) reduced the bacterial load in the blood and tissues of infected mice. Meanwhile, treatment with phage JF1 relieved the pathological symptoms observed in each tissue. Furthermore, levels of the inflammatory cytokines TNF-α, IFN-γ and IL-6 in the blood of infected mice were significantly (P < 0.01) decreased in the phage-treated group. Taken together, these results indicate that phage JF1 demonstrated great potential as an alternative therapeutic treatment against T. pyogenes infection.